A site-differentiated [4Fe–4S] cluster controls electron transfer reactivity of Clostridium acetobutylicum [FeFe]-hydrogenase I. Issue 16 (1st April 2022) - Lubner, Carolyn E.; Artz, Jacob H.; Mulder, David W.; Oza, Aisha; Ward, Rachel J.; Williams, S. Garrett; Jones, Anne K.; Peters, John W.; Smalyukh, Ivan I.; Bharadwaj, Vivek S.; King, Paul W.
Abstract : Histidine coordination of the distal [4Fe–4S] cluster in [FeFe]-hydrogenase was demonstrated to tune the cluster spin-states, spin-pairing and surrounding molecular orbitals to enable more facile electron transfer compared to cysteine coordination. Abstract : One of the many functions of reduction–oxidation (redox) cofactors is to mediate electron transfer in biological enzymes catalyzing redox-based chemical transformation reactions. There are numerous examples of enzymes that utilize redox cofactors to form electron transfer relays to connect catalytic sites to external electron donors and acceptors. The compositions of relays are diverse and tune transfer thermodynamics and kinetics towards the chemical reactivity of the enzyme. Diversity in relay design is exemplified among different members of hydrogenases, enzymes which catalyze reversible H2 activation, which also couple to diverse types of donor and acceptor molecules. The [FeFe]-hydrogenase I from Clostridium acetobutylicum (CaI) is a member of a large family of structurally related enzymes where interfacial electron transfer is mediated by a terminal, non-canonical, His-coordinated, [4Fe–4S] cluster. The function of His coordination was examined by comparing the biophysical properties and reactivity to a Cys substituted variant of CaI. This demonstrated that His coordination strongly affected the distal [4Fe–4S] cluster spin state, spin pairing, and spatial orientations of molecular orbitals, with a minor effect on reduction potential. The deviations in these properties by substituting His for Cys in CaI, correlated with pronounced changes in electron transfer and reactivity with the native electron donor–acceptor ferredoxin. The results demonstrate that differential coordination of the surface localized [4Fe–4S]His cluster in CaI is utilized to control intermolecular and intramolecular electron transfer where His coordination creates a physical and electronic environment that enables facile electron exchange between electron carrier molecules and the iron–sulfur cluster relay for coupling to reversible H2 activation at the catalytic site.